تعليم الصّرف للمبتدئين باستخدام قاموس المنوّر في المعهد الإسلامي السّلفي - Anwar, Mohammad Sofi; Assidiqi, Ali Hasan; Ainy, Nurul (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2023)
One of the questions that often arises in learning shorof for beginners is how to determine the chapter of the fi'il that will be recited. This is certainly a difficulty for students who have never studied shorof before. For this reason, the presence of the al Munawwir dictionary is important to help students overcome these difficulties. Because the al munawwir dictionary contains fi'il madhi, mudhori', and mashdar. This research is a qualitative descriptive research which aims to describe shorof learning for beginners using the al munawwir dictionary in Islamic boarding schools. The data in this research was collected through documentation studies and analyzed using the Miles and Hubberman model. The results of this research show the role of the al Munawwir dictionary as a learning resource and medium, the procedures for using the dictionary to look for the meaning of a word, and how to use the al Munawwir dictionary in learning shorof for beginners. سؤال من الأسئلة التي غالبًا ما تنشأ في تعلم الصَّرْف للمبتدئين هي كيفية تحديد فصل الفعل الذي سيتم تصريفه. فطبعاً هذه هي من الصّعوبات للطلاب الذين لم يدرسوا الصَّرْف من قبل. ومن هنا، حضور قاموس المنوّر له أمرًا مهمًا لمساعدة الطّلاب على حلّ صعوبة هذه. يحتوي قاموس المنور على الأفعال الماضية والمضارعة والمصدر. تعتبر هذه الدراسة بحثًا وصفيًا كيفيًا الذي يهدف إلى وصف تعليم الصَّرْف للمبتدئين باستخدام قاموس المنوّر في المعهد السّلفي. تم جمع البيانات في هذا البحث من خلال الدراسات الوثائقية وتحليلها باستخدام نموذج مايلز وهابرمان. تُظهر نتائج هذا البحث دور قاموس المنور كمورد ووسيلة للتعلم، وكيفية استخدام القاموس للبحث عن معنى كلمة، وكيفية استخدامه في تعليم الصَّرْف للمبتدئين.